1312 Characteristics of Those Who Present with Self-Inflicted Burns: A Burns Unit Service Evaluation Which Challenges Stereotypes. (12th October 2021) - Magness, C; Kang, M; Kennedy, M; Alexander, S; O'Boyle, C; Hasham, S; Shepherd, L
Abstract: Introduction: Self-harm rates in the UK are increasing. Healthcare professionals' beliefs regarding repeat attendance; attention-seeking; and poor treatment compliance may contribute to patients' stigma. Self-inflicted burns (SIB) constitute a minority of burns cases, but require disproportionate healthcare input, yet little is known about these patients. Our aim was to evaluate presentations, compliance and outcomes in this patient group. Method: A retrospective audit of outpatients with SIBs attending a UK Burns Unit over four years (Jan 2016-Dec 2019). Results: Over the study period, 58 patients presented with 94 burn wounds. Incidence doubled over one year (2018-2019). Most patients were female (85%) with a median age of 29 years (range 19-62). The most commonly associated psychiatric diagnosis was personality disorder. On presentation 22% (n = 21) were admitted under the Mental Health Act. For 83% (n = 48) it was their first presentation with a SIB, although 74% had previously presented with non-burn self-harm. Median burn size was 0.5% TBSA, the most common mechanism was contact (48%) and 77% were deep (n = 77). 92% were compliant with treatment and did not tamper with their wounds or dressings. Conclusions: The majority, 70% (n = 41), of patients only presented once to the Burns Department during the study period. This challenges the commonly held stereotype that those who self-harm will also seek attention through repeat presentation. Ongoing education among health professionals may dispel some myths regarding these individuals. Further, larger investigations, may permit rigorous comparison of treatment outcomes with non-SIB patients.